Abnormal Signatures Recorded by FORMOSAT-2 and FORMOSAT-3 over South Atlantic Anomaly and Polar Region - Tsung-Ping Lee; Panthalingal Krishnanunni Rajesh; Chao-Yen Chen; Jann-Yenq Liu; Chen-Joe Fong; Jar-Chen Pon; Shan-Kuo Yang; Guey-Shin Chang (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
Computer systems onboard FORMOSAT-2 (F2) and FORMOSAT-3/COSMIC (F3/C) satellites often register abnormal signatures which are recorded as automatic reconfiguration orders (ARO) in F2, and reboot/reset (RBS) in F3/C. The ARO and RBS spatial distribution counts recorded since the launch of satellites is investigated to identify regions of anomalous events. Data from the star tracker onboard F2 and Tiny Ionosphere Photometer (TIP) onboard F3/C are also analyzed. The results show that the F2 ARO and F3/C RBS cluster over the SAA (South Atlantic Anomaly) region and also over the poles, which suggest that high energy particles bombarding the satellite electronics play an important role.